Philosophy as world literature - Di Leo, Jeffrey R. (New York, NY, USA Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2022)
"Explores the intersections between philosophy and literature through a transnational, comparative lens"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Literature -- Philosophy